Performance of gypsum sheathed CFS panels under combined lateral and gravity loading. (July 2020) - Ayatollahi, Seyed Reza; Usefi, Nima; Ronagh, Hamid; Izadinia, Mohsen; Javaheri, Mohammad Reza
Abstract: This paper investigates the performance of gypsum sheathed cold-formed steel (CFS) shear wall panels under combined action of lateral and gravity loading. The influence of gravity load on the lateral performance of the wall panels is experimentally evaluated through two scenarios of service and design levels. For this purpose, a total of eight full-scale one-side sheathed CFS panels, with two different field screw spacings as well as single and double section chord stud conditions, are considered for the experimental program. Based on the test results, a discussion on different failure modes, load-displacement relationships, maximum shear capacity, maximum displacement at failure, stiffness and energy absorption of the wall panels is presented. The test results are also employed to evaluate the response modification factor (R factor) of the wall panels using two different methods. The results indicate that the wall panels under gravity load at design level can provide higher shear strength, energy absorption and stiffness, but lower ductility compared to wall panels under service gravity load. In addition, the effect of increasing gravity load is more significant when double-section chord is employed for the specimens. The values of the response modification factor also indicate that the method of measuring R factor can relatively affect the results. Highlights: The effect of gravity load on the lateral performance of CFS walls sheathed with gypsum board is investigated. Increasing the gravity load enhances the shear resistance, stiffness and energy absorption of the wall panel. R factor for panels under service gravity load is higher than walls under gravity load at the design level.